TUGAS DAN WEWENANG BALAI BESAR PENGAWASAN OBAT DAN MAKANAN DALAM MENGAWASI MAKANAN YANG MENGANDUNG ZAT BERBAHAYA - DIYAN SETIAWAN (Fakultas Hukum Universitas Narotama, 2020)
This research is motivated by the problem of food which is a basic human need that cannot be left behind in everyday life. The method used in conducting this research is to use the normative type, namely examining the duties and authority of the POM Agency / Balai POM against the applicable regulations. The approach method is carried out by linking tasks from several applicable regulations, and is assisted by interviews. The results of the research in the form of what tasks are carried out by the POM Agency / Balai POM to control food containing hazardous materials, show that the tasks carried out are in accordance with applicable laws and regulations, namely Presidential Regulation Number 80 of 2017 concerning the Food and Drug Administration Agency, as a Technical Implementers within the POM Agency, then their duties are regulated in the Regulation of the Head of the POM Number 12 of 2018 concerning the Organization and Work Procedures of the Technical Implementing Units within the POM Agency. Other research results explain the actions taken in controlling food containing hazardous materials, there are 3 (three) pillars of the system, namely: the producer supervision system, the government supervision system and the consumer control system. The form of supervision carried out by the POM Center is Pre-Market and Post-Market supervision. Keywords: Duties, Authorities, Supervision, Dangerous Food